Faktor Risiko terjadinya Cedera pada Anak Usia Sekolah Dasar - Susy Kuschithawati, Rahadyan Magetsari, Nawi Ng (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Every year many children all over the world become disabled or die because of injury. It is estimated that 98% of child mortality is caused by injury, and this mostly happens in low and middle income countries. Injury may happen accidentally or intentionally and internally (from the children themselves) or externally (from environmental factors).Objective: The objective of the study was to identify the seriousness and types of injury and risk factors of injury occurrence among elementary school children at Yogyakarta Municipality.Methods: The study used school-based cross sectional design and was conducted at 28 elementary schools of Yogyakarta municipality with as many as 4690 children of grade I – VI as subject of the study. Samples were taken using multistage cluster sampling technique. Dependent variables consisted of injury that took place at schools, home and the surrounding and absence from school, whereas independent variables consisted of age and sex of children, age of mothers, social and economic status, home environment and time. Research instruments used were questionnaires to get data of injury risk factors and impact of injury and observation sheets to assessschool environment.Results: Injury prevalence was as much as 42.56% (mild injury 36,89% and severe injury 5,7%) . Factors related to injury occurrence among elementary school children were sex (OR=1.31; 95% CI 1.16 – 1.47) and home environment (OR=2.76; 95% CI 1.36 – 6.62). Types of injury that often happened to elementary school children were scratches, bruises, sprains, bites, flesh wounds burns, road accidents, broken bone and small particles infiltration.Conclusion: Home environment was an important factor of injury occurrence among elementary school children. Therefore preventive action had to be taken by improving home and environment security, and alerts of parents in order that occurrence of injury could be avoided. Sex of children was also an important factor of cause for injury occurrence among elementary school children.Keywords: injury among children, risk factors, prevalence